(untitled) (RENTAS: Jurnal Bahasa, Sastera dan Budaya, 2024)
Character education must be instilled, one of which is through learning with teaching materials containing multicultural-based character education. In the Indonesian School of Singapore (SIS), Indonesian students use a textbook by the publisher Erlangga as their teaching resource. The book is not designed for Indonesian students studying Indonesian at Indonesian Schools Abroad (ISA), although character education is urgently needed. Therefore, this study should be carried out to analyze the elements of character education in the book. This study aimed to analyze character education in multicultural-based Indonesian language teaching materials at SIS. The study design is of content analysis. Research data was obtained through questionnaires, and textbook documents of the Erlangga Publisher were analyzed according to the theory of Greene and Petty (2007). The results of the needs analysis show that the SIS teachers strongly agree with fourteen (14) aspects of character education in Bahasa Indonesia (BI) teaching materials, 10 aspects of good BI textbooks, and 4 multicultural aspects of BI teaching materials, and agree with one aspect of character education in BI teaching materials. This study concludes that the need to develop a character education model in multicultural-based Indonesian language teaching materials is also required by SIS to achieve the vision and mission of SIS.